Trabalho e gênero: Proteção e desproteção das mulheres pescadoras da cidade de Bayeux, Paraíba. - Bezerra, Maria do Socorro de Pontes (2015)
This dissertation has to study labor relations and gender with artisanal fisherwomen in the city of Bayeux, Paraíba. Deals with contemporary overlaps with infers the study of labor relations and gender with artisanal fisherwomen in the city of Bayeux, the White House community on the banks of river paroeira, Paraíba River Estuary affluent. In Chapter I, we aim to show the importance of gender relations, its inequalities in the labor market, especially in the artisanal fishing activity. As well as the advances and challenges that permeate the theme in order to understand how was the process of historical construction, sociocultural and socioeconomic. In Chapter II we seek to make visible feminist perspectives from the encouragement and advancement of public policies for the economic freedom of women, as well as the role of women in society and their inclusion in the capitalist production system. And in Chapter III, stand out: life story, free interviews, semi-structured, and direct observation; within the research, the data were analyzed by interpreting the speech of the interviewees, based on the union model of the various individual skills. The knowledge that these women have about the quality of life, from what is protection and lack of protection in its territory constitutes a tool to support the incorporation of public policy implementation plans and socioeconomic development of the territory.